Communicable Diseases Intelligence volume 14 issue 4 - 26 February 1990 - whole issue - No author listed (Communicable Diseases Intelligence, 1990)
Whole-issue pdf, comprising: Viruses, Chlamydias, Coxiellas, Rickettsias and Mycoplasmas Reporting Scheme Overseas briefs Original article Salmonella outbreaks, Australia - January to September 1989 (Based on the National Salmonella Surveillance Scheme (NSSS) Quarterly Reports, Issue 7/89 dated October 1989, and 8/89 dated November 1989) Update: Ebola-related filovirus infection in nonhuman primates and interim guidelines for handling nonhuman primates during transit and quarantine. [further update in CDI 90/9 page 11-13] Reporting Tables: Australia - Communicable Diseases Intelligence Period 1/2/90 to 14/2/90